Improving the use of available feed resources to overcome sheep feeding deficits in western China - Philp, Joshua; Komarek, Adam M.; Pain, Sarah J.; Li, Xueling; Bellotti, William D. (Commonwealth Scientific and Industrial Research Organisation, 2016)
Socioeconomic and agro-ecological circumstances often compel smallholder livestock farmers in the developing world to maintain livestock over winter, and this can incur production penalties due to insufficient feed quality and availability. Recent policy efforts in western China have attempted to address this issue through the promotion of lucerne production to support growing livestock numbers with its high nitrogen content, however lucerne is underutilised by farmers and rarely maintained beyond harvest. The potential benefits to production of storing enough lucerne to meet the minimum nitrogen requirements of rumen function during the winter deficit were explored in an experiment in Qingyang Prefecture, Gansu Province, P.R. China. Tan weaner sheep (mean weight 15.4 kg) were fed corn straw, corn grain and lucerne hay in respective ratios of 80 : 20 : 0 [metabolisable energy (ME) = 7.4 MJ/kg DM, crude protein = 40 g/kg DM; ‘R1’] or 55 : 20 : 25 (ME = 8.2 MJ/kg DM, crude protein = 65 g/kg DM; ‘R2’). Rations were offered daily in a constant quantity that supplied ~80% maintenance energy requirements at the start of the experiment. Sheep fed R2 retained 0.7 kg more on average than those fed R1 (P < 0.01) after 20 days under experimental conditions with a mean weight change of –0.089 kg/day for R1 and –0.055 kg/day for R2 (P < 0.01). Sheep fed R1 experienced a sustained loss in digestive function over time, with ration DM digestibility decreasing by 0.56% per day (P < 0.01, R2 = 0.65), and MJ of ME per kg of ingested DM (M/D) decreasing by 0.06 MJ/kg DM per day (P < 0.001, R2 = 0.98). The mean M/D of R1 had fallen to 6.1 after 20 days (P < 0.01). The mean DM digestibility and M/D observed in R2-fed animals remained comparatively stable, with no statistically significant differences between starting and finishing values (P > 0.05). The results indicate that the capacity for underfed Tan weaner sheep to absorb energy from low protein rations typical of winter rapidly degrades and that the lucerne hay in the diet prevented this decline. Furthermore, these findings demonstrate that conserving lucerne for inclusion in winter rations is a potential strategy for smallholder farmers to maintain the digestive efficiency of Tan sheep during sustained underfeeding contributing to greater retention of liveweight on restricted diets.